2018
DOI: 10.1093/milmed/usy028
|View full text |Cite
|
Sign up to set email alerts
|

Building Capacity for Complementary and Integrative Medicine Through a Large, Cross-Agency, Acupuncture Training Program: Lessons Learned from a Military Health System and Veterans Health Administration Joint Initiative Project

Abstract: The ATACS program provided a foundational template to increase CIM across the MHS and VHA. The lessons learned in the program's implementation will aid future CIM training programs and improve program evaluations. Future work is needed to determine the most efficient means of improving CIM credentialing and privileging procedures, standardizing and adopting uniform CIM EHR codes and documentation, and examining the effectiveness of CIM techniques in real-world settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…Recently the military received a grant to train military providers in battlefield acupuncture (BFA), a standardized auricular therapy protocol, to aid in reducing the reliance on opioids in the military 50. While they were successful in training more than 2500 clinicians, less than 30% of trainees could practice BFA on returning to their institutions, due to barriers in licensing, credentialing, and supervision 51…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently the military received a grant to train military providers in battlefield acupuncture (BFA), a standardized auricular therapy protocol, to aid in reducing the reliance on opioids in the military 50. While they were successful in training more than 2500 clinicians, less than 30% of trainees could practice BFA on returning to their institutions, due to barriers in licensing, credentialing, and supervision 51…”
Section: Discussionmentioning
confidence: 99%
“…In states where specific training requirements are minimal, choosing a standardized protocol, such as BFA, may be an efficient strategy to get your program started. BFA, with just five ear points, can be taught in 1 day with high post-course skills confidence 51 52. It can easily be taught to physicians and physician extenders alike, expanding the number of providers able to offer treatment 51.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VA and active military settings have implemented battlefield acupuncture (BFA), a rapid auricular acupuncture protocol that involves inserting semipermanent needles on 5 specific points. 23 25 Anecdotal and early scientific evidence has demonstrated that BFA can significantly and immediately reduce pain symptoms 26 28 and is effective for treating both chronic and acute pain. 27 However, research on BFA’s impact on pain is limited to a few studies with small sample sizes.…”
mentioning
confidence: 99%
“… 27 , 28 Because of the simplicity of the protocol, it is easy to administer and can be performed by multiple types of providers. 24 , 25 , 27 On the basis of early scientific evidence, starting in 2016, the Veterans Health Administration (VHA) has trained over 2800 providers to deliver BFA. 29 …”
mentioning
confidence: 99%